RETRACTED: Development of Biorational Management Package of Root Knot Nematode Disease of Country Bean - Faruk, Iqbal (Journal of Agronomy Research, 2022)
This article has been retracted on 10 November 2022. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2639-3166.jar-25-5841) A field experiment was conducted with a view to test the efficacy of Tricho-composts and integration of Tricho-composts, poultry refuse (PR), neem oilcake (NOC), saw dust burning (SDB) with chemical nematicide Furadan 5G (Carbofuran) for controlling root knot nematode of country bean through which growers will be benefited. The root-knot nematode infested soils were treated with Tricho-compost-1 @ 2 kg/pit, Tricho-compost-2 @ 2 kg/pit, Tricho-compost-1 @ 2 kg/pit + Furadan 5 G @ 20 g/pit, Tricho-compost-2 @ 2 kg/pit + Furadan 5 G @ 20 g/pit, poultry refuse @ 5-6 kg/pit + Furadan 5 G @20 g/pit , neem oil cake @ 500 g/pit + Furadan 5 G @ 20 g/pit and saw dust burning + Furadan 5 G @ 20 g/pit. It was revealed that all the treatments performed well in reducing root-knot nematode infestation and increasing plant growth and yield country bean compared to farmers’ practices. Among the treatments, integration of poultry refuse with Furadan 5G or Trichoderma based bio-fungicides Tricho-composts with Furadan 5G or neem oil cake with Furadan 5G are the best treatments in reducing root-knot nematode infestation and increasing plant growth as well as yield of country bean. Soil treatment with only Tricho-composts or integration of saw dust burning with Furadan 5G also performed better in reduction of root knot nematode disease and increasing plant growth as well as yield of country bean.
Keywords: Trichoderma; Tricho-compost; poultry refuse; neem oilcake; Furadan 5G; Meloidogyne incognita; Dolichos lablab